Influence of changes in wetland inundation extent on net fluxes of carbon dioxide and methane in northern high latitudes from 1993 to 2004 - Qianlai Zhuang; Xudong Zhu; Yujie He; Catherine Prigent; Jerry M Melillo; A David McGuire; Ronald G Prinn; David W Kicklighter (Environmental Research Letters, 2015)
Estimates of the seasonal and interannual exchanges of carbon dioxide (CO _2 ) and methane (CH _4 ) between land ecosystems north of 45°N and the atmosphere are poorly constrained, in part, because of uncertainty in the temporal variability of water-inundated land area. Here we apply a process-based biogeochemistry model to evaluate how interannual changes in wetland inundation extent might have influenced the overall carbon dynamics of the region during the time period 1993–2004. We find that consideration by our model of these interannual variations between 1993 and 2004, on average, results in regional estimates of net methane sources of 67.8 ± 6.2 Tg CH _4 yr ^−1 , which is intermediate to model estimates that use two static inundation extent datasets (51.3 ± 2.6 and 73.0 ± 3.6 Tg CH _4 yr ^−1 ). In contrast, consideration of interannual changes of wetland inundation extent result in regional estimates of the net CO _2 sink of −1.28 ± 0.03 Pg C yr ^−1 with a persistent wetland carbon sink from −0.38 to −0.41 Pg C yr ^−1 and a upland sink from −0.82 to −0.98 Pg C yr ^−1 . Taken together, despite the large methane emissions from wetlands, the region is a consistent greenhouse gas sink per global warming potential (GWP) calculations irrespective of the type of wetland datasets being used. However, the use of satellite-detected wetland inundation extent estimates a smaller regional GWP sink than that estimated using static wetland datasets. Our sensitivity analysis indicates that if wetland inundation extent increases or decreases by 10% in each wetland grid cell, the regional source of methane increases 13% or decreases 12%, respectively. In contrast, the regional CO _2 sink responds with only 7–9% changes to the changes in wetland inundation extent. Seasonally, the inundated area changes result in higher summer CH _4 emissions, but lower summer CO _2 sinks, leading to lower summer negative greenhouse gas forcing. Our analysis further indicates that wetlands play a disproportionally important role in affecting regional greenhouse gas budgets given that they only occupy approximately 10% of the total land area in the region.